Evidence in personal injury proceedings : papers presented at a seminar held in Sydney on 27 February 2003 - Hall, Justine (Justine Wendy) (Legalwise Seminars, 2003)
Examines the factors to consider when assessing economic loss including business structures and financial statements. Asseses the needs of injured persons and the impact of Workers' Compensation and Motor Accident legislation and explores psychiatric and psychological injury, changes to legislation and new impairment rating scale.